Evaluation of Gait Variable Change over Time as Transtibial Amputees Adapt to a New Prosthesis Foot. (20th May 2019) - Zhang, Xueyi; Fiedler, Goeran; Liu, Zhicheng
Abstract : A variety of prescribed accommodation periods have been used in published prosthesis intervention studies that have examined biomechanical outcomes. Few investigators included repeated measurements in their study design, leaving questions as to how measured outcomes change as amputees acclimate to a new prosthesis. This paper is the product of our investigation as to whether measured gait variables were affected by the duration of accommodation period, and to assess the relationship between measured outcomes and the subjective perception of the participants. A sample of transtibial amputees were recruited for this study. Gait data was collected by wearable sensor repeatedly, starting immediately after fitting the interventional foot and extending over a subsequent four days. Participants indicated their perceived accommodation quality on a visual analog scale (VAS). A total of twelve commonly used spatiotemporal gait parameters were analyzed. Friedman tests were used to determine overall differences across time points in both early (one hour) and late (day two through five) accommodation phases, for each gait variable. Statistically significant changes across the early phase were found for variables gait speed χ 2 (2)=8.000, p =0.018, cadence χ 2 (2)=7.185, p =0.028, and double support time on the sound side χ 2 (2)=8.615, p =0.013. Across days two through five, no gait variable significantly changed. VAS scores correlated strongly with step count (r=1.000, p <0.001) and cadence (r=0.857, p =0.014). Longer accommodation periods resulted in less deviations of gait variables for the clinical assessment in the process of prosthetic rehabilitation. Trying out prosthetic interventions for less than one hour has yielded unreliable outcomes.